Platelet derived growth factor promotes the recovery of traumatic brain injury by inhibiting endoplasmic reticulum stress and autophagy-mediated pyroptosis - Wu, Fangfang; Zhang, Renkan; Meng, Weiyang; Liu, Lei; Tang, Yingdan; Lu, Leilei; Xia, Leilei; Zhang, Hongyu; Feng, Zhiguo; Chen, Daqing (Frontiers in Pharmacology, 2022)
Autophagy and endoplasmic reticulum stress(ER stress) is important in numerous pathological processes in Traumatic Brain Injury(TBI).Growing evidence have indicated that pyroptosis-mediated inflammasome is involved in the pathogenesis of TBI.Platelet derived growth factor(PDGF) has been reported to as a potential therapeutic drug for neurological diseases.However, the roles of PDGF,autophagy and ER stress in pyroptosis have not been elucidated in the TBI. This study investigated the roles of ER stress and autophagy after TBI at different time points. We found that the ER stress and autophagy after TBI were inhibited, the expressions of pyroptosis-related proteins induced by TBI, such as NLRP3, Pro-Caspase1, Caspase1,GSDMD,GSDMDP30,and IL-18, were decreased upon PDGF treatment. Moreover, the rapamycin (RAPA, an autophagy activator) and tunicamycin (TM, an ER stress activator) eliminated the PDGF effect on the pyroptosis after TBI. Interestingly, the sodium 4-phenylbutyrate (4-PBA, an ER stress inhibitor) suppressed autophagy but 3-methyladenine (3-MA, an autophagy inhibitor) not for ER stress. The results revealed that PDGF improved the functional recovery after TBI, and the effects were markedly reversed by TM and RAPA. Taken together, this study provides a new view that PDGF is a potential therapeutic strategy for enhancing the recovery of TBI.